2016
DOI: 10.1002/cbic.201500688
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal X‐ray and Infrared Imaging of an Organometallic Derivative of Praziquantel in Schistosoma mansoni

Abstract: An organometallic derivative of praziquantel was studied directly in worms by using inductively coupled plasma-mass spectrometry (ICP-MS) for quantification and synchrotron-based imaging. X-ray fluorescence (XRF) and IR absorption spectromicroscopy were used for the first time in combination to directly locate this organometallic drug candidate in schistosomes. The detection of both CO (IR) and Cr (XRF) signatures proved that the Cr(CO)3 core remained intact in the worms. Images showed a preferential accumulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

7
3

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Interestingly, some rutheniumclotrimazole (Ctz) complexes displayed high levels of in vitro activity against Leishmania major and Trypanosoma cruzi and low levels of toxicity when their activities were assessed in normal mammalian cells (28). In addition to ruthenium, other organometallic complexes have also been reported to display interesting antiparasitic and/or anti-infective activities (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). For instance, one manganese(I) tricarbonyl complex, [Mn(CO) 3 (bpy R,R )(Ctz)]PF 6 (where bpy R,R is 2,2=-bipyridine), showed submicromolar activity against Staphylococcus aureus and Staphylococcus epidermidis with MICs of 0.625 M. Moreover, the related complex [Mn(CO) 3 (bpy R,R )(Ktz)]PF 6 (where Ktz is ketoconazole) was active against Trypanosoma brucei with an IC 50 of 0.7 M, while the IC 50 for mammalian cells was more than 10 times higher (43).…”
mentioning
confidence: 99%
“…Interestingly, some rutheniumclotrimazole (Ctz) complexes displayed high levels of in vitro activity against Leishmania major and Trypanosoma cruzi and low levels of toxicity when their activities were assessed in normal mammalian cells (28). In addition to ruthenium, other organometallic complexes have also been reported to display interesting antiparasitic and/or anti-infective activities (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). For instance, one manganese(I) tricarbonyl complex, [Mn(CO) 3 (bpy R,R )(Ctz)]PF 6 (where bpy R,R is 2,2=-bipyridine), showed submicromolar activity against Staphylococcus aureus and Staphylococcus epidermidis with MICs of 0.625 M. Moreover, the related complex [Mn(CO) 3 (bpy R,R )(Ktz)]PF 6 (where Ktz is ketoconazole) was active against Trypanosoma brucei with an IC 50 of 0.7 M, while the IC 50 for mammalian cells was more than 10 times higher (43).…”
mentioning
confidence: 99%
“…As a serious note of caution, Lay and co‐workers have demonstrated that chromium(III) complexes with labile ligands can be transformed to carcinogenic chromium(VI) species in adipocytes . We note also that organometallic chromium(0) complexes have been used for medicinal applications . To the best of our knowledge, photocytotoxicity studies of chromium(III) complexes have not yet been reported.…”
Section: Introductionmentioning
confidence: 79%
“…The presence of a rhenium atom in the Re(CO) 3 probe makes it useful for X-ray fluorescence (XRF) imaging. 38,41,46 Additionally, the presence of an NhatN moiety with low lying π* orbitals coordinated with an Re(I) center renders the probe fluorescent through a metal to ligand charge transfer band and useable in luminescence studies, 30,4749 and finally, the presence of three highly polar C–O bonds makes it detectable in vibrational (IR and Raman) spectroscopies. 37,47,50 The three modalities can be combined in the same analysis thanks to the existence of materials for sample holding such as Si 3 N 4 .…”
Section: Introductionmentioning
confidence: 99%